2013
DOI: 10.3344/kjp.2013.26.3.255
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Pre-emptive Administration of Ketamine and norBNI on Pain Behavior, c-Fos, and Prodynorphin Protein Expression in the Rat Spinal Cord after Formalin-induced Pain Is Modulated by the DREAM Protein

Abstract: BackgroundWe investigated the effects of pre-emptive administration of ketamine and norBNI on pain behavior and the expression of DREAM, c-Fos, and prodynorphin proteins on the ipsilateral side of the rat spinal cord at 2 and 4 hours after formalin injection.MethodsEighty-four male Sprague Dawley rats were divided into 4 major groups consisting of control rats (C) (n = 12), rats given only formalin injections (F) (n = 24), and rats treated with pre-emptive administration of either ketamine (K+F) (n = 24) or no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…It is the reason for sacrificing the rats at three days after formalin injection. Thoracotomy and perfusion fixation technique was performed to expose rats spinal cord according to our previous study [27]. The lumbar enlargement of L4-L5 spinal cord segment were sectioned (40 μm thickness) using a cryostat and sections were rinsed with Tris-buffered saline (TBS) twice for 5 min each and incubated overnight at 4°C with primary mouse monoclonal antibody for OX-42 protein (microglia protein marker) diluted to 1:500 in buffer (mixture of TBS with 2% normal goat or horse serum and 0.2% Triton-X) followed by incubation with biotinylated horse anti-mouse IgG (for microglia protein) diluted at 1:200 in buffer (mixture of TBS with 2% normal goat/horse serum and 0.2% Triton-X) for 1 h with gentle agitation at room temperature.…”
Section: Immunohistochemistry For Microglial Expressionmentioning
confidence: 99%
“…It is the reason for sacrificing the rats at three days after formalin injection. Thoracotomy and perfusion fixation technique was performed to expose rats spinal cord according to our previous study [27]. The lumbar enlargement of L4-L5 spinal cord segment were sectioned (40 μm thickness) using a cryostat and sections were rinsed with Tris-buffered saline (TBS) twice for 5 min each and incubated overnight at 4°C with primary mouse monoclonal antibody for OX-42 protein (microglia protein marker) diluted to 1:500 in buffer (mixture of TBS with 2% normal goat or horse serum and 0.2% Triton-X) followed by incubation with biotinylated horse anti-mouse IgG (for microglia protein) diluted at 1:200 in buffer (mixture of TBS with 2% normal goat/horse serum and 0.2% Triton-X) for 1 h with gentle agitation at room temperature.…”
Section: Immunohistochemistry For Microglial Expressionmentioning
confidence: 99%
“…For these reasons, the pharmacological inhibition of DREAM may represent an interesting new analgesic strategy for the treatment of pain because of the lack of typical side-effects of opioids. Moreover, formalin injections cause an increase in DREAM protein expression in the spinal cord of rat models of inflammatory pain [69], showing a possible feedback regulation of DREAM expression by inflammatory pain. In addition, more recently, it was found that the N-terminal 31-50 fragment of DREAM interacts with transient receptor potential vanilloid 1 (TRPV1) and reduces its surface localization in the rat dorsal root ganglia.…”
Section: Dream and Neuropathic Painmentioning
confidence: 94%
“…Meanwhile, the duration of time (seconds) the rat spent licking the injected paw was recorded for up to 60 min. The data was then summed for phase 1 (acute pain and peripheral actions: 0 to 10 min post-formalin injection), early phase 2 (early chronic pain and central actions: 15 to 35 min), and late phase 2 (late chronic pain and central actions: 40 to 60 min) [25].…”
Section: Formalin Induced Flinching and Licking Behaviourmentioning
confidence: 99%